PENGARUH MODAL SOSIAL TERHADAP KETAHANAN KELUARGA MISKIN DI BANTARAN KALI CILIWUNG - Prayitno, Ujianto Singgih (Jurnal Aspirasi, 2012)
Variousissues in social are common amongst the urban poor. Similarly, areas along the banks of Ciliwung River are regularly face the risk of flooding. Quantitative approach was usedto investigate the role of social capital in increasing the economic resilience of poor families along the banks of Ciliwung River. The results showed that collective action and willingness to work together are two instrumental variables in predicting families’ resilience, followed by information and communication variables, as well as by the actors compare to by communities along the banks which gave greater role in families’ economic resilience.